2020
DOI: 10.2174/1570178617666200320104923
|View full text |Cite
|
Sign up to set email alerts
|

Arylhydrazono/Aryldiazenyl Pyrazoles: Green One-Pot Solvent-Free Synthesis and Anticancer Evaluation

Abstract: Aims: The aim of this study was to synthesize and evaluate the biological activity of newer pyrazole derivatives. Background: Cancer is one of the world's top noncommunicable disease growing rapidly with an approximately 18.1 million new cases and 10 million deaths in the last year. Despite the availability of numerous classes of anticancer agents, treatment for all types of cancers is still a long way due to severe adverse drug reactions and drug resistance. Therefore, there is a pressing need to develop n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…After obtaining interesting results with arylhydrazonopyrazole analogues, different substitutions were made at the phenyl ring for optimizing the template. e analogues 1 and 2 were prepared by using the method described earlier [8].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After obtaining interesting results with arylhydrazonopyrazole analogues, different substitutions were made at the phenyl ring for optimizing the template. e analogues 1 and 2 were prepared by using the method described earlier [8].…”
Section: Resultsmentioning
confidence: 99%
“…Compound 2 was found to be moderately effective, with IC 50 values of 94.2 ± 0.3, 34.6 ± 2.6, and 17.3 ± 0.5 μ M against the MCF-7, HepG2, and HCT-116 cell lines, respectively. Our previous studies have shown that unsubstituted phenyl derivative of aryldiazenyl pyrazole had a poor antiproliferative activity (IC 50 > 100 μ M) against all three cell lines [ 8 ]. This finding indicates that substitution with electron withdrawing groups such as bromo and nitro groups significantly improved the anticancer potential of aryldiazenyl pyrazole derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations